The incidence of congenital malformations in children with cancer - Mutafoğlu-Uysal, Kamer; Günes, Dilek; Tüfekçi, Ozlem; Kalelihan-Cankal, Aydan; Sarialioğlu, Faik; Olgun, Nur (The Turkish Journal of Pediatrics, 2009)
We evaluated the incidence of congenital malformations in 566 children (median age: 8, M:F 1.3) with lymphomas and solid tumors using patient records. In this study, 12.7% of children either had a congenital malformation (7.8%) or a birthmark (4.9%). The incidence of patients with a childhood cancer syndrome was 3% and these cases developed typical tumors. The rate of consanguineous marriages was 12.6%, and family history of cancer was positive in 31.2%. Median age at cancer diagnosis, gender, maternal age, history of stillbirth and missed abortion, consanguinity of parents, and family history of cancer were not significantly different in cases with and without a congenital malformation. The most frequent cancers were central nervous system tumors and lymphomas. No remarkable association between a particular anomaly and a specific cancer type could be shown. The high incidence of congenital anomalies in this study may stimulate future large cohort studies in our country.